TP53 PIN3 and MDM2 SNP309 polymorphisms as genetic modifiers in the Li–Fraumeni syndrome: impact on age at first diagnosis. Issue 11 (18th June 2009) - Marcel, V; Palmero, E I; Falagan-Lotsch, P; Martel-Planche, G; Ashton-Prolla, P; Olivier, M; Brentani, R R; Hainaut, P; Achatz, M I
Abstract : Background: Li–Fraumeni and Li–Fraumeni-like syndromes (LFS/LFL), characterised by the development of multiple early onset cancers with heterogeneous tumour patterns, are associated with germline TP53 mutations. Polymorphisms in the TP53 pathway ( TP53 PEX4 at codon 72, rs1042522; MDM2 SNP309, rs2279744) have modifier effects on germline TP53 mutations that may account for the individual and familial diversity of tumour patterns. Methods and results: Four polymorphisms were analysed in a series of 135 Brazilian LFS/LFL cancer patients (32 TP53 mutation carriers and 103 wild-type subjects). We report for the first time that another polymorphism in the TP53 gene, TP53 PIN3 (rs17878362), has a strong modifier effect on germline TP53 mutations. This polymorphism, which consists of a 16 bp duplication in intron 3 (A1, non-duplicated allele; A2, duplicated allele), is associated with a difference of 19.0 years in the mean age at the first diagnosis in TP53 mutation carriers (n = 25, A1A1: 28.0 years; n = 7, A1A2: 47.0 years; p = 0.01). In addition, cancer occurrence before the age of 35 years is exclusively observed in A1A1 homozygotes. In this series, the effect of TP53 PEX4 and MDM2 SNP309 on age at diagnosis was similar to the one reported in other series and was smaller than the one of TP53 PIN3 ( TP53 PIN3: difference of 19.0 years; TP53 PEX4: 8.3 years; MDM2 SNP309: 12.5 years). Conclusion: These results suggest that TP53 PIN3 is another polymorphism in the TP53 pathway that may have a modifier effect on germline TP53 mutations and may contribute to the phenotypic diversity of germline TP53 mutations associated with LFS/LFL patients.